EVALUASI POTENSI SUMBER DAYA AIR DI PROVINSI GORONTALO - Wahjono, Heru Dwi (Jurnal Air Indonesia, 2005)
Gorontalo as a new province has many natural resources. One of the natural resource at Gorontalo Province that support society live is water resource. Because of the condition of natural, most of people in Gorontalo Province live as farmer and fisherman. On the other side this new province also has been developing many infrastructures and basic tools for irrigation and watering such as water channel, water dam, irrigation network, etc. The recording process of water resource assets that belong to this new province has been done every year by local government through the Gorontalo Province Water Resources Management Department. The water resource management system is computerized system that able to inventory water resources at Gorontalo Province in two river area development units, so the water resources potential in this province canÃ‚Â  be retrieved easily and quickly.Ã‚Â Katakunci : sumber daya air, prasarana dan sarana air, sistem pengelolaan data, potensi sumber daya airÃ‚Â